Analisis Teks Bacaan pada Buku SD Kelas IV Kurikulum Merdeka - Sabila Zanjabila Trisna; Dadan Djuanda; Diah Gusrayani (Jurnal Pena Ilmiah, 2022)
This research was conducted based on the importance of teaching materials used during learning at school. Analysis of student textbooks is important so that the learning objectives in the curriculum can be met. In this study, it examined the readability of he text, the structure of the text, the profile of Pancasila students and the realm of questions. The method used is a qualitative method with analytical descriptive studies. The subject in this study is a book of elementary school students. From the results of the study, it is known that as many as 25% of a total 24 texts are at levels 5, 6, 7. For the structure of the text, the text that has a complete structure is as much as 83%. Then as many as 37%, containing profiles of Pancasila students with global diversity. There are 43% that are included in the realm of LOTS and as many as 57% that are included in the realm of HOTS.